2011
DOI: 10.1101/cshperspect.a004424
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress and Its Functional Link to Mitochondria: Role in Cell Survival and Death

Abstract: The endoplasmic reticulum (ER) is the primary site for synthesis and folding of secreted and membrane-bound proteins. Proteins are translocated into ER lumen in an unfolded state and require protein chaperones and catalysts of protein folding to assist in proper folding. Properly folded proteins traffic from the ER to the Golgi apparatus; misfolded proteins are targeted to degradation. Unfolded protein response (UPR) is a highly regulated intracellular signaling pathway that prevents accumulation of misfolded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
268
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(282 citation statements)
references
References 88 publications
6
268
0
3
Order By: Relevance
“…44 The mitochondrial Ca 2+ overload generated leads to the depolarization of the inner membrane, the release of cytochrome c release and the activation of caspases. 45 In line with the reported occurrence of mitochondrial fission during ER stress [46][47][48] and the role of Drp1 in ER stress-induced apoptosis of pancreatic β-cells, 49 we found that PKA activation led to Drp1 inhibition, as monitored by Drp1 phosphorylation. Moreover, we demonstrated that PKA activation and Drp1 inhibition protected cells from apoptotosis induced by Tu but not by TNF or Eto, thereby identifying a direct mechanistic link for the protective effect of PKA activation in cells undergoing ER stress.…”
Section: Discussionsupporting
confidence: 70%
“…44 The mitochondrial Ca 2+ overload generated leads to the depolarization of the inner membrane, the release of cytochrome c release and the activation of caspases. 45 In line with the reported occurrence of mitochondrial fission during ER stress [46][47][48] and the role of Drp1 in ER stress-induced apoptosis of pancreatic β-cells, 49 we found that PKA activation led to Drp1 inhibition, as monitored by Drp1 phosphorylation. Moreover, we demonstrated that PKA activation and Drp1 inhibition protected cells from apoptotosis induced by Tu but not by TNF or Eto, thereby identifying a direct mechanistic link for the protective effect of PKA activation in cells undergoing ER stress.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, knockdown of either of the key autophagic genes, ATG5 or ATG7, impacted on CASP8 activation and cell death induction, highlighting the crucial role of autophagy in the activation of this novel endoplasmic reticulum stress-induced death pathway [34]. The endoplasmic reticulum stress is responsible for enhanced cancer cell proliferation and IRE1 knockdown by a dominant-negative construct of IRE1 (dnIRE) resulted in a significant anti-proliferative effect on glioma growth [35,36].…”
mentioning
confidence: 99%
“…The activation of endoplasmic reticulum stress is indispensable for tumor growth as it facilitates adaptation to stressful environmental conditions [40]. IRE1 is the most evolutionary conserved sensor that responds to protein misfolding with a highly tuned program aimed to either resolve the stress or direct the cell towards apoptosis in case stress becomes too severe, which makes it a key regulator of cell life and death processes [35,40]. Recently, we have shown that glutamine deprivation affects the expression of proliferation related genes in U87 glioma cells and that IRE1 knockdown modifies glutamine deprivation effects on these genes expression possibly contributing to suppression of glioma cells proliferation [41].…”
mentioning
confidence: 99%
“…T he endoplasmic reticulum stress is an important component of tumor growth, including glioblastoma multiforme, which is a highly aggressive tumor with very poor prognosis, and to date, there is no efficient treatment available [1][2][3]. Diffuse infiltrating gliomas are the most common tumors of the central nervous system.…”
mentioning
confidence: 99%